Sign-Changing Solutions for Kirchhoff-Type Problems with Variable Exponent - Changmu Chu; Ying Yu (Journal of Mathematics)
This paper is devoted to study a class of Kirchhoff-type problems with variable exponent. By means of the perturbation technique, the method of invariant sets for the descending flow and necessary estimates and the existence of infinitely many sign-changing solutions to this problem are obtained.